The reckoning - Peckham, Caroline; Valenti, Susanne (Peckham, Caroline. Zodiac Academy, 2025)
At Zodiac Academy, twin sisters face brutal senior hazing, high-stakes exams, and a looming Lunar Eclipse, all while uncovering a dark conspiracy and realizing their enemies may be far closer than theyhad imagined.